2010
DOI: 10.1051/0004-6361/201014893
|View full text |Cite
|
Sign up to set email alerts
|

Testing the theory of grain growth and fragmentation by millimeter observations of protoplanetary disks

Abstract: Context. Observations at sub-millimeter and mm wavelengths will in the near future be able to resolve the radial dependence of the mm spectral slope in circumstellar disks with a resolution of around a few AU at the distance of the closest star-forming regions. Aims. We aim to constrain physical models of grain growth and fragmentation by a large sample of (sub-)mm observations of disks around pre-main sequence stars in the Taurus-Auriga and Ophiuchus star-forming regions. Methods. State-of-the-art coagulation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
119
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(131 citation statements)
references
References 32 publications
11
119
1
Order By: Relevance
“…local pressure maxima due to turbulent vortices or spiral density waves, have been invoked. Birnstiel et al (2010b) have compared the observed fluxes at millimeter wavelengths for the disks samples described in R10 and in this paper with Fig. 7.…”
Section: Grain Growthmentioning
confidence: 96%
See 1 more Smart Citation
“…local pressure maxima due to turbulent vortices or spiral density waves, have been invoked. Birnstiel et al (2010b) have compared the observed fluxes at millimeter wavelengths for the disks samples described in R10 and in this paper with Fig. 7.…”
Section: Grain Growthmentioning
confidence: 96%
“…The observed flux of the fainter disks are instead typically overpredicted even by more than one order of magnitude. These discrepancies may be explained by considering in the disk models a dust reduction due to radial drift at a reduced rate 14 or during an earlier evolutionary time or due to efficient conversion of dust into larger, unseen bodies (see Birnstiel et al 2010b for more details). Observations of these faint disks can thus help us to determine which mechanisms play a major role for the dynamics and evolution of large grains in the outer regions of disks.…”
Section: Grain Growthmentioning
confidence: 99%
“…Scattered light images of the circumstellar disk surrounding the T Tauri star IM Lupi may indicate the presence of fluffy aggregates (Pinte et al 2008). Birnstiel et al (2010) and Ricci et al (2010Ricci et al ( , 2012 used porous spherical grains to specify the dust opacity in a sample of young protoplanetary disks. For a general study of the influence of porosity on the dust opacity in protoplanetary disks, see Semenov et al (2003).…”
Section: Introductionmentioning
confidence: 99%
“…It also implies that pebbles are constantly replenished: they are lost to the inner disk, but drift in from the outer disk. Pebble accretion, in contrast to planetesimal accretion, is therefore a global phenomenon: one has to consider the evolution of the dust population throughout the entire disk (Birnstiel et al 2010;Okuzumi et al 2012;Testi et al 2014). …”
Section: Pebblesmentioning
confidence: 99%